Indonesian, Korean, and French Sheet Masks: Three Alternatives in a Hybrid Choice Model of Indonesian Women's Choice Decision - Ferica, Michelle; Belgiawan, Prawira Fajarindra; Mayangsari, Lidia; Windasari, Nila Armelia; Laila, Nisful; Persada, Satria Fadil; Nasution, Reza Ashari (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
Women's choice decision has gained lots of attention in the literature, particularly regarding how they evaluate attributes that are similarly important. The Indonesian skincare market is one of the most attractive markets, not only for local but also global producers of skincare products. This paper aims to provide an in-depth analysis of factors that affect Indonesians when they choose facial sheet masks (SM) from three countries—Indonesia, South Korea, and France—and to examine respondents' preferences with regard to local or imported SM products. This study used a mixed method, starting with exploratory research to find the levels of attribute for each alternative. A hybrid choice model is later established with Python Biogeme to find significant factors, demand elasticities, and willingness to pay. From its exploratory research, this study ascertained several attributes such as price, packaging, quality, brand, refreshing effect, halal essence, and attitudes. This study found that price, quality, refreshing effect, halal essence, and attitude significantly influence SM choice decisions from the discrete choice. The results fill a gap in the literature by comprehensively examining product properties and attitudes that affect women's decisions regarding skincare products. It also contributes—particularly for the skincare industry and marketers—to further improve the SM market share, particularly in the Indonesian and Southeast Asian markets.